Off-pump coronary artery bypass grafting in left main stem stenosis: outcomes, concerns and controversies - Athanasopoulos, Leonidas V. (J Thorac Dis, 2016)
Left main stem (LMS) disease is known to be a poor prognostic factor in terms of morbidity or mortality. Traditionally, it has been treated with constitution of bypass to provide required haemodynamic stability. We searched the literature for evidence on off-pump (OFP) surgery for treating this high-risk group of patients focusing in our review on postoperative outcomes, concerns and controversies. The majority of the studies identified showed favourable or equal outcomes of OFP when compared to conventional approach. All of the studies, apart from two, which showed lower incidence of postoperative deaths, demonstrated equal mortality rates. Stroke rates were found less in three studies. Less blood transfusions, inotropic use and length of study has been also demonstrated. The main concerns of OFP surgery are: haemodynamic instability and less complete revascularization. Main controversies are: same or favourable outcomes despite lower number of grafts with OFP surgery and less stroke rates despite manipulation of aorta with side-clamping. Despite these concerns and controversies OFP surgery has been proven to be feasible and safe as demonstrated by results from numerous studies.